Metrik Finsler Pseudo-Konveks Kuat pada Bundel Vektor Holomorfik - ,, Haripamyu; ,, Jenizon; Arnawa, I Made (Jurnal Matematika; Vol 7 No 1 (2017)DO - 10.24843/JMAT.2017.v07.i01.p78, 2017)
Abstract : Rizza-negativity of holomorphic vector bundle  is a sufficient condition for the negativity of . In the present paper, we shall discuss that as a special case, using the Rizza metric  which is derived from a Hermitian metric  also implies the negativity of . Further we showed that for the negative holomorphic vector bundle there is a pseudo-convex Finsler metric with negative curvature. Keywords : Hermitian metric, Rizza metric, Rizza-negativity.